The Impact of Alternative Government Policies Under Varying Exchange Systems: Comment - Michaely, Michael (Quarterly Journal of Economics, 1968)
Journal Article The Impact of Alternative Government Policies under Varying Exchange Systems: Comment Get access Michael Michaely Michael Michaely Hebrew University of Jerusalem and National Bureau of Economic Research Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 3, August 1968, Pages 508–510, https://doi.org/10.2307/1879522 Published: 01 August 1968